Effectiveness Usual Counseling by Pharmacist of RSUD A.W. Sjahranie Samarinda to Improve Medication Compliance in Hypertension - Welinda Dyah Ayu; Victoria Yulita; Dewi Rahmawati (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Compliance to antihpertensive medications represents a success factor for blood pressure control in clinical practice. Medical non-compliance has been identified as a major public health problem in the treatment of hypertension. This study evaluated an additional usual counseling could achieve optimal BP control. This experimental study uses cohort study design using prospective patient data collection in patients with hypertension, and hypertension with complications at RSUD A.W.Sjahranie SAMARINDA from Juli 2014-Oktober 2014. Data were collected by interviews and questionnaires; meanwhile the patient's blood pressure data were taken from the medical record. A total of 61 patients. The results showed that there were not significant different in change BP control and compliance level wilcoxcon (p>0,05). The compliance status in usual counseling relatively poor. Phamacist counseling are important to improve medication compliance in hypertension